The Kavango-Zambezi Conservation Area (KAZA) and its dynamics in Zambia - Lupiya, Astridah (Department of Environmental and Geographical Science, 2020)
Transfrontier conservation areas (TFCAs) have emerged as one of the 21st century’s contemporary approaches to management of natural resources which span the borders of two or more countries. Robust arguments exist that boundaries hamper the conservation objectives of migratory species. On the basis of the claimed potential of TFCAs to reconcile the conservation and economic development objectives of nations through tourism, TFCAs have been widely embraced in Southern Africa as a model for governing shared resources. TFCAs in Southern Africa have been motivated by both ecological and socio-economic factors, TFCAs are also politically motivated. This study uses the lens of political ecology to understand the motivation of Zambia’s participation in the Kavango–Zambezi TFCA (KAZA TFCA). KAZA TFCA is one of the largest TFCAs in the world and is said to be home to the largest number of the remaining African elephants (approximately 120,000). This five-country TFCA spans large rural landscapes that are a potential site for extensive tourism and currently provide livelihood opportunities for many poor rural households. This study assesses the investments of Zambia’s government in the KAZA TFCA. It uses the case study of Simalaha Community Conservancy in the Western Province of Zambia to examine the implications of the KAZA TFCAs on the local population in the conservancy. The research uses semi-structured interviews, field observations and secondary data to advance an argument that TFCAs do not always yield positive gains for both governments and local communities. Gains depend on several factors, such as level of development of a country, level of tourism development and the preparedness of a participating nation to invest in and benefit from a TFCA. The study establishes that KAZA is an unequal investment landscape, with Zambia being one of the lesser investors in the KAZA TFCA. In addition, the notion that the TFCA model embodies the poverty reduction objectives meant to benefit local populations is contestable as the KAZA on the Zambian side (Simalaha community) has not improved the welfare of the local people.